Implementation of Progressive Law in Sharia Banking Dispute Settlement: Case Study of Religious Court Decisions in Indonesia - Nur Hidayah; Abdul Azis (Universitas Islam Negeri Mataram, 2023)
This research aims to analyze the extent to which judges have applied progressive legal paradigm in deciding Sharia banking disputes and the extent to which the decisions have fulfilled the principles of legal certainty, justice, and value. This normative legal research uses statutory and case study approaches by analyzing Sharia banking dispute decisions obtained from the website of the Supreme Court of the Republic of Indonesia. This research found that decisions based on textual legal interpretations tend to less implement progressive law, lacking of accommodating people's sense of justice as they put more emphasis on legal certainty. Meanwhile, decisions based on contextual legal interpretations tend to implement progressive law by prioritizing legal justice rather than legal certainty, more accommodating people’s sense of justice. Such different decisions are partly attributed to the different interpretations of judges due to different levels of competence and different understanding of Sharia among the judges. By participating in integrated and sustainable training, judges can improve their competence to deleiver justice for all concerned parties.